Southscapes : Geographies of Race, Region, and Literature - Davis, Thadious M., 1944- (Book collections on Project MUSE., 2011)
"By interpreting segregation as the central experience for twenty-first century southern literature (just as slavery was for an earlier generation of writers) and by theorizing the interconnected aspects of racial and spatial constructions in the formation of the nation, Davis shows us a way to understand black space--social, spatial, and artistic arenas of creativity--not just in terms of exclusion and of pushing back/reacting against, but as sites of memory and imagination far beyond wounds and danger"--Provided by publisher.